Synergistic Emission Reduction of Particulate Pollutants in Coal-fired Power Plants Using Ultra-low Emission Technology - Leixing Tao; Yanyan Wang; Chunmei Yue; Zhigang Shen; Zhichao Liu; Qizhen Liu; Junchao Lu; Jian Wang; Honglei Ding; Weiguo Pan (Aerosol and Air Quality Research)
Abstract The total particulate matter (TPM) is a crucial indicator when evaluating flue gas emissions from coal-fired units. TPM contains solid and liquid contaminants and condensable particulate matter (CPM), which is mainly composed of sulfate and various anions, cations, and metal ions. This study selected three typical large-capacity coal-fired power plants in Shanghai retrofitted with ultra-low emission technology and monitored their emissions of PM2.5, SO3, and CPM during power generation. The results showed that the plants achieved comprehensive removal rates of 99.689−99.878% and 86.99−92.92% for PM2.5 and SO3, resulting in emitted concentrations of approximately 0.99−1.79 and 1.91−2.50 mg m−3, respectively, which are considerably lower than those associated with the traditional flue gas process. Additionally, a significant decrease in the emitted filterable particulate matter (FPM) caused a simultaneous decrease in CPM. After being equipped with the ultra-low emission technology, the units displayed a 76% reduction in the emitted FPM concentration and a smaller FPM/CPM ratio (1:2 vs. 1:1). The emitted TPM (the sum of CPM and FPM) was reduced by 82%, with an average measured concentration of 7.36 ± 3.56 mg m−3. The values we obtained are representative and provide basic data for environmental assessment and local environmental policy formulation.